Barn swallow antipredator behavior covaries with melanic coloration and predicts survival. (24th July 2018) - Costanzo, Alessandra; Romano, Andrea; Ambrosini, Roberto; Parolini, Marco; Rubolini, Diego; Caprioli, Manuela; Corti, Margherita; Canova, Luca; Saino, Nicola
Abstract : Conspecific individuals may differ in "personality traits, " including antipredator behavior, and individual fitness variation can depend on personality. In this study, barn swallows were subjected to a restraint-handling protocol and their behavioral response was recorded. Individuals were consistent in agitation upon repeated manipulations, reflecting antipredator behavior. More agitated females, but not males, had larger survival until the next breeding season and, in both sexes, more agitated individuals showed darker ventral plumage coloration. Abstract: Conspecific individuals often consistently differ in their behavioral responses to specific exogenous stimuli. Such individual differences in "personality" have been shown to be heritable, suggesting that selection maintains variation in personality. However, survival selection on a major personality trait, antipredator behavior, and its sex-dependency, has been seldom measured in the wild. Here, we found that yearling barn swallows ( Hirundo rustica ) showed consistency in agitation upon repeated exposure to a restraint-handling protocol, probably reflecting antipredator behavior, and that males were more agitated than females. Females that exhibited larger antipredator behavior were more likely to survive until the next breeding season with no variation among 3 study years nor across 7 breeding colonies, suggesting that variation in antipredator behavior is not maintained by spatiotemporal variation in viability selection on antipredator behavior. In both sexes, the intensity of melanin-based ventral plumage coloration positively covaried with antipredator behavior, consistent with previous observations from diverse vertebrate species. In some barn swallow populations, male coloration is targeted by directional intersexual selection, suggesting that melanization signals antipredator behavior to prospecting females and that sexual selection for antipredator behavior, or other correlated personality traits, can drive the evolution of sexual color dimorphism in barn swallows. Thus, we showed that viability selection occurs on antipredator behavior and that spatiotemporal variation in selection has no major role in promoting variation in antipredator behavior. More melanized individuals were more agitated, implying that melanization may signal personality in a sexual communication context in a species where male coloration is an epigamic trait.